Escin Sodium Improves the Prognosis of Acute Pancreatitis via Promoting Cell Apoptosis by Suppression of the ERK/STAT3 Signaling Pathway. (13th August 2021) - Zhang, Qian; Zhao, Chen; Zhang, Lei; Sun, Kai; Yu, Linlin; Wang, Xianming; Ren, Lei; Zhang, Nan; Chen, Chengyu; Liu, Ju; Wang, Haimei; Tian, Hu
Abstract : Acute pancreatitis (AP), an inflammatory disorder of the pancreas, can cause systemic inflammatory responses. Escin Sodium (ES), a natural mixture of triterpene saponins extracted from the dry ripe fruit of Fructus Aesculi or horse chestnut crude, has been demonstrated to have antiedematous, anti-inflammatory, and antiexudative effects. We here aim to investigate the effects of ES pretreatment on AP in vivo and in vitro and explore its potential molecular mechanism. In the present study, we demonstrated that ES pretreatment could apparently decrease amylase and lipase, downregulate inflammatory cytokines, and attenuate pancreatic damage. Additionally, the increased expression of apoptotic-related proteins and the results of flow cytometry demonstrated the effects of ES on promoting apoptosis in acinar cells. Moreover, ES could enhance mitochondrial membrane potential (MMP, ΔΨ m) and reactive oxygen species (ROS) level and reduce intracellular calcium concentration, which are closely related to mitochondrial-mediated death. The effect of ES pretreatment on acinar cell apoptosis was furtherly confirmed by the regulatory pathway of the ERK/STAT3 axis. These results suggest that ES attenuates the severity of AP by enhancing cell apoptosis via suppressing the ERK/STAT3 signaling pathway. These findings provide evidence for ES which is treated as a novel and potent therapeutic for the treatment of AP.